Empowering Older Adults through Smart Home Automation for Better Quality of Life - Pereira, Antonio Jorge Oliveira; Paula, Franciele Alessandra de; Melo, Thalia Bianca da Silva; Carvalho, Dárlinton B. Feres; Viana, Matheus Carvalho (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2024.241704, 2024)
Population ageing comes with multifaceted challenges that stretch beyond health-related advancements and demographic shifts. Older adults are confronted by significant healthcare obstacles, requiring special needs, remarkably in their home environment. The present study draws upon Smart Home Automation technology to develop an Ambient Assisted Living (AAL) prototype aimed at enhancing daily living activities, health monitoring and independence for older adults, thereby improving their overall quality of life. Employing the Design Science Research (DSR) method of research combined with the Double Diamond process of design, this study intends to create and evaluate a solution particularly tailored to the needs of older adults, furthering a more safe and dignified ageing experience.